2019
DOI: 10.2478/eko-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Landscape Use on Water Quality of the Žitava River

Abstract: Intensification of landscape use brings along the negative effects on environmental components. These include surface water pollution. The aim was to determine the effect of landscape use on the water quality of the Žitava river. It was assumed that an area with the high proportion of anthropogenic activity would negatively affect water quality. At the same time, we assumed that an area with the lower proportion of anthropogenic use and with the higher proportion of natural and semi-natural elements contribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Solanki (2012) reported that agricultural field runoffs are one of the major causes of nitrate input into the water body. Petlušová et al (2019) in a similar study pointed out that pollution of water is caused by the current and dominant anthropogenic activities in the area. Chapman (1996) reported that nitrate values above 5 mgL −1 is an indication of pollution resulting from organic sources.…”
Section: Resultsmentioning
confidence: 91%
“…Solanki (2012) reported that agricultural field runoffs are one of the major causes of nitrate input into the water body. Petlušová et al (2019) in a similar study pointed out that pollution of water is caused by the current and dominant anthropogenic activities in the area. Chapman (1996) reported that nitrate values above 5 mgL −1 is an indication of pollution resulting from organic sources.…”
Section: Resultsmentioning
confidence: 91%
“…Higher values of TDS recorded for the Akor River between April and June 2019 could probably be due to active various farming activities such as clearing, ploughing and ridge making in the farmlands around the river (Petlušová et al, 2019). Additionally, heavy runoffs as a result of early rainfall during these months may also have contributed immensely to these higher values.…”
Section: Physical-chemical Parametersmentioning
confidence: 95%
“…In particular, water quality from the sources of non-centralized water supply has been studied in the US by Zheng, Flanagan (2017) and Schaider et al (2019) (in particular, the report by DeSimone et al, 2009 indicated that more than one in five [23%] domestic wells contained one or more contaminants at a concentration greater than a human health benchmark), in the shallow wells of Keiyo Highlands (Kenya) by Mbaka et al (2017), in Ireland by Hooks et al (2019), in Tai'an City (China) by Wu-yuan (2010), in Pakistan by Daud et al (2017), in eastern Slovakia by Sasakova et al (2018), and in Limpopo Province (South Africa) by Edokpayi et al (2018). A number of researchers have studied the factors that have impact on water quality (Khatri, Tyagi, 2014) and assessed it by the content of specific pollutants such as nitrates (Schaider et al, 2019;Petlušová et al, 2019), arsenic (Shiber, 2005;Zheng, Flanagan, 2017), and heavy metals (Edokpayi et al, 2018). Gibson and Kelsey Water Quality Improvement Strategy (2017) and the implementation of individual components (Malecki et al, 2017;Eggers et al, 2018) are also worth noting.…”
Section: Introductionmentioning
confidence: 99%